Silicon-based negative electrode binder of double-conduction ion network with self-repairing function and preparation method thereof
By synthesizing the aqueous silicon-based anode adhesive with a two-step method in the silicon-based anode material of lithium-ion batteries, the adhesive has strong dynamic repair network and dual-conducting ion effect characteristics, solving the problem of adhesive fracture caused by volume expansion, extending the battery's cycle life and improving fast charging performance.
Patent Information
- Application Number
- CN202411994766.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The volume expansion of the silicon-based anode material of existing lithium-ion batteries causes the adhesive to break during charging and discharging, affecting the battery's cycle life and fast charging performance.
The aqueous silicon-based negative electrode adhesive synthesized by a two-step method has strong dynamic repair network and dual-conducting ion effect characteristics. Polyvinyl alcohol as the main body, ether bonds are introduced by acetalization reaction, and polyion monomer side chains are introduced through graft polymerization reaction to build a highly robust, dynamically reversible coordination bond network.
The binder can adapt and suppress volume changes through breaking and recombination of dynamic bonds when the volume of the active material changes, avoid slipping and breaking of binder molecules, extend the cycle life of the battery, and improve the fast charging performance of the battery by improving ionic conductivity.
Smart Images

Figure CN119899321A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery preparation, and relates to a silicon-based negative electrode binder with a dual ion-conducting network having a self-repairing function and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have gradually become one of the preferred carriers for providing and storing energy due to their advantages such as high energy density, long cycle life and green environmental protection. However, with the continuous expansion of applications, the market has put forward higher requirements for the cycle life and fast charging performance of lithium-ion batteries. Silicon-based negative electrode materials have ultra-high specific capacity, which can greatly improve the energy density of lithium-ion batteries, but there are still difficulties such as excessive volume expansion of active materials and insufficient intrinsic conductivity of materials. Binders play the role of bonding active materials and base materials in negative electrode sheets, which is crucial to the stability and cycle life of batteries. In order to cope with volume expansion, patent CN110444765A designed a non-dynamic three-dimensional cross-linked structure binder by chemically cross-linking polyvinyl alcohol. Although it can temporarily suppress the volume expansion of active materials, it cannot cope with the breakage of binders under long cycles. Patents CN113782744A, CN114203987A and CN112680148A all use hydrogen bonding between PVA and other component polymers to form a cross-linked network structure to stabilize the long cycle of the battery, and lack consideration of the conductivity of the binder. Patent CN114242990A uses polyvinyl alcohol polymer and acrylic acid-acrylamide-(2-acrylamide-2-methylpropanesulfonic acid) terpolymer to form a three-dimensional interconducting network structure binder. Although the terpolymer has a certain effect of promoting the diffusion of ion conductivity, polyvinyl alcohol is still in a state of being less than lithium ions, which is not conducive to the overall lithium ion diffusion of the electrode. Similarly, in patent CN110336037B, polyvinyl alcohol, polydopamine and poly (3,4-ethylenedioxythiophene): polystyrene sulfonate aqueous solution (PEDOT:PSS) are used to form a composite binder system, and polyvinyl alcohol has no effect on the diffusion of lithium ions.
[0003] How to provide the comprehensive performance of the binder so that while ensuring the bonding strength of the binder, it can optimize the ion conductive pathway to reduce impedance and improve fast charging performance, and combine the dynamic network characteristics to extend the battery cycle life has become an important issue that needs to be solved urgently. Summary of the invention
[0004] In view of this, in view of the application limitations of the above-mentioned lithium-ion batteries and the shortcomings of the current development of silicon-based negative electrode materials, the present invention takes the binder, an important component of the silicon negative electrode plate, as the starting point for optimizing battery performance. The invention provides a new polymer synthesized by a two-step method and used as a water-based silicon negative electrode binder and a preparation method thereof, wherein the binder has a strong dynamic repair network and has dual ion-conducting effect characteristics. The dynamic repair characteristics can better adapt to the volume change of the active material during the charge and discharge process on the premise that the binder plays a bonding role on the active material, the conductive agent, etc. Under the volume expansion and contraction of the active material, the binder can use the breaking and reorganization of the dynamic bonds to dissipate energy, adapt to and inhibit the volume change of the active material, and avoid the fragmentation of the active material due to volume change after multiple charge and discharge, and the slippage and breaking of the binder molecules that cause the battery plate to fail. The main chain and side chain of the polymer binder have functional group structures with lithium ion conductivity characteristics, which will improve the ion conductivity by constructing a fast ion-conducting network in the plate, which is beneficial to the battery rate performance and cycle performance.
[0005] In order to solve the above-mentioned technical problems, the present invention provides a method for preparing a silicon-based negative electrode binder with a dual ion-conducting network with self-repairing function. The water-based binder uses hydroxyl-rich polyvinyl alcohol as the molecular skeleton, provides excellent bonding performance, and introduces an ether bond structure with a lithium ion conducting effect into the molecular chain through acetalization, and further utilizes graft polymerization to introduce ionic monomers to construct comb-shaped side chains with high energy and breakable and recombinable properties. The ionic functional groups can promote the dissociation of lithium salts and the migration of lithium ions, thereby accelerating the conduction of lithium ions.
[0006] The method of the invention takes polyvinyl alcohol as the main body, introduces ether bonds into chain segments by acetalization reaction, and then introduces polyion monomer side chains into the polyvinyl alcohol acetal by graft polymerization reaction.
[0007] The following steps are involved:
[0008] (1) Preparation of polyvinyl acetal binder:
[0009] Place polyvinyl alcohol into deionized water and stir continuously, slowly increase the temperature to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol aqueous solution. When the temperature is adjusted to the first treatment temperature, add hydrochloric acid solution to the first pH value. Then, slowly add a quantitative specific concentration of aldehyde solution and keep it warm for a period of time. After the reaction is completed, the pH of the reaction system is adjusted to neutral. When the temperature drops to the second treatment temperature, add an appropriate amount of urea to remove unreacted aldehyde substances. After cooling to room temperature, pour out the reactants, dialyze using a dialysis bag, and freeze-dry the dialyzed polymer solution for later use; the amount of aldehyde substance added is 5% to 40% of the molar number of hydroxyl groups in polyvinyl alcohol;
[0010] (2) Polyvinyl acetal grafted ionomer:
[0011] The polyvinyl alcohol acetal polymer obtained by the above reaction is redissolved in deionized water. Then add an appropriate amount of initiator, replace the air three times under vacuum, and heat the reactor to the set reaction temperature. After the temperature is constant and the system is stirred evenly, control the dropwise addition time and slowly add the monomer solution to carry out the graft polymerization reaction. After the reaction lasts for 6 to 24 hours (preferably 12 hours), stop the reaction. After cooling to room temperature, pour out the reactant, dialyze using a dialysis bag, and freeze-dry the dialyzed polymer solution for later use.
[0012] In the above method, the raw material in step (1) is characterized by polyvinyl alcohol with different polymerization degrees and hydrolysis degrees having a polyhydroxy structure. Further, the degree of polymerization of the polyvinyl alcohol is in the range of 600 to 2500.
[0013] Furthermore, the hydrolysis degree of the polyvinyl alcohol as described above ranges from 50% to 99%, preferably from 60% to 99%.
[0014] In the above method, the conversion degree of hydroxyl groups in the acetalization reaction by using aldehyde substances is 5% to 50%.
[0015] In the above method, the aldehyde substance has an aldehyde structure, and the aldehyde structure includes one or more of formaldehyde, acetaldehyde, propionaldehyde, butyraldehyde and the like.
[0016] In the above method, the graft polymerization uses an initiator to initiate the monomer to carry out graft polymerization on the polyvinyl alcohol acetal chain, and the mass ratio of the grafting body to the grafting monomer is 10:1 to 1:10; the mass ratio of the initiator to the monomer is 1:1000 to 5:100.
[0017] In the above method, the first treatment temperature in step (1) is 50-100°C.
[0018] In the above method, the first pH value in step (1) is 1-6.
[0019] In the above method, the dropping time in step (1) is 5 to 60 minutes; and the reaction time is 1 to 6 hours.
[0020] In the above method, the concentration of the aldehyde solution in step (1) is 5% to 60%.
[0021] As in the above step (1), the mass ratio of the polyvinyl alcohol to the aldehyde substance is 5:1 to 20:1.
[0022] Furthermore, the types of the aldehyde substance include but are not limited to one or more of formaldehyde, acetaldehyde, propionaldehyde, and butyraldehyde.
[0023] As in the above step (1), the second treatment temperature is 30-70°C.
[0024] As in the above step (1), the second pH value is 7-10.
[0025] Furthermore, the alkaline solution for adjusting pH includes, but is not limited to, one or more of LiOH, NaOH, KOH, NaOH, and NH3·H2O.
[0026] As in the above step (2), the reaction temperature is 50-100°C; the dropwise addition time is 5-120 min; and the total reaction time is 1-12 h.
[0027] Furthermore, the initiator includes but is not limited to one or more of ammonium persulfate, potassium persulfate, alkali metal persulfate (ammonium, potassium)-reducing agent (sodium bisulfite (NaHSO3), sodium sulfite (Na2SO3), sodium thiosulfate (Na2S2O3), oxalic acid, etc.), azobisisobutylamidine hydrochloride (AIBA), azobisisobutylimidazoline hydrochloride (AIBI), azobiscyanovaleric acid (ACVA), and azobisisopropylimidazoline (AIP).
[0028] As in the above step (2), the monomer includes but is not limited to one or more of dimethyldiallylammonium chloride (DMDAAC), methacryloyloxyethyltrimethylammonium chloride (DMC), acryloyloxyethyltrimethylammonium chloride (DAC), methacrylamidopropyltrimethylammonium chloride (MAPTAC), 2-acrylamido-2-methylpropanesulfonic acid (AMPS), acrylic acid (AA), itaconic acid (IA), sodium styrene sulfonate (NaSS), sodium α-olefin sulfonate, 2-methacryloyloxyethylphosphorylcholine (MPC), carboxybetaine acrylamide (CBAA), methacrylic acid sulfobetaine (SBMA), and methacrylic acid carboxybetaine (CBMA).
[0029] As in the above step (2), the reaction temperature is 50-100°C.
[0030] As in the above step (2), the reaction time is 1 to 12 hours.
[0031] As in the above step (2), the mass ratio of the polyvinyl alcohol acetal polymer to the monomer is 10:1 to 1:10.
[0032] The above method is used to prepare a silicon-based negative electrode binder with a dual ion-conducting network having a self-repairing function. The water-based binder uses coordination bonds to form a three-dimensional network structure and has self-repairing properties, and uses the reversible dynamic properties of coordination bonds to cope with the volume changes of negative electrode particles during the cycle. The rupture of coordination bonds can dissipate the energy of volume expansion and avoid the slippage and rupture of binder molecules.
[0033] Compared with the existing technology, the present invention has the following significant and substantial advantages and features:
[0034] (1) The present invention adopts water as a solvent and a carrier of the reaction system as a whole, and the reaction is simple, the product yield is high, and it has outstanding advantages such as environmental friendliness and low production process cost.
[0035] (2) The flexibility of the polyvinyl alcohol main chain and the hydroxyl groups provide a beneficial adhesion effect, and the acetalization of the hydroxyl groups introduces abundant ether bonds. On the one hand, the affinity for the electrolyte is improved, and on the other hand, the dissociation of ion pairs in the lithium salt and the transfer of lithium ions are promoted.
[0036] (3) By using the hydroxyl active sites to graft ionic monomers, high bond energy and dynamically reversible coordination bonds are obtained, which redistributes the charge density distribution of the side groups, enhances the intermolecular forces, and constructs a highly entangled dynamic three-dimensional cross-linked network. The large number of ionic functional groups on the molecular side chains build a fast pathway for the movement of lithium ions through electrostatic interactions and chain segment movement.
[0037] Advantages of the present invention will be partially set forth in the following description, and partly will be obvious from the description, or may be learned through implementation of the embodiments of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 is the Coulomb efficiency diagram;
[0039] Figure 2 A circular data graph. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solution and advantages of the invention clearer, the technical solution will be described more clearly and in detail in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the present invention, not all embodiments. Based on the embodiments of the present invention, other embodiments obtained by professionals in this field without creative work should belong to the protection scope of the present invention.
[0041] Example 1
[0042] (1) Preparation of polyvinyl formal binder:
[0043] Put 10g of polyvinyl alcohol (1799) into 100g of deionized water and stir continuously. Slowly heat to 90℃ and keep warm for 1h to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol aqueous solution. Adjust the temperature to 85℃, and start dripping dilute hydrochloric acid solution (0.1mol / L) to adjust the pH to about 2.5. Slowly drip 3.5g of formaldehyde aqueous solution (35wt%), dripping time: 30min, and keep warm for 120min. After the reaction is completed, use sodium hydroxide solution (1wt%) to neutralize the reaction system to a pH of about 7. Lower the temperature to 60℃, add 1.5g of urea and react for 30min to remove the unreacted part of the unreacted formaldehyde. After cooling to room temperature, pour out the reactant, dialyze using a dialysis bag, and freeze-dry the dialyzed polymer solution for later use.
[0044] (2) Polyvinyl formal grafted ionomer:
[0045] Redissolve 10g of the polyvinyl alcohol acetal polymer obtained by the above reaction in 100g of deionized water. Add 0.1g of potassium persulfate to the reactor containing the polyvinyl alcohol formal polymer solution, replace the air three times with vacuum and purge with nitrogen for 30min, and heat the reactor to 75°C. After the temperature is constant and the system is stirred evenly, control the dropwise addition time to 30min, and slowly add 3g of methyl methacrylate sulfobetaine for graft polymerization. After the reaction has reacted for 12h, stop the reaction. After cooling to room temperature, pour out the reactant, dialyze with a dialysis bag, and freeze-dry the dialyzed polymer solution for later use.
[0046] Example 2
[0047] This embodiment is basically the same as embodiment 1, except that the amount of main chain ether bonds introduced into the polyvinyl alcohol is regulated by controlling the amount of formaldehyde and the acetalization time.
[0048] (1) Preparation of polyvinyl formal binder:
[0049] Put 10g of polyvinyl alcohol (1799) into 100g of deionized water and stir continuously. Slowly heat to 90℃ and keep warm for 1h to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol aqueous solution. Adjust the temperature to 85℃, and start dripping dilute hydrochloric acid solution (0.1mol / L) to adjust the pH to about 2.5. Slowly drip 2g of formaldehyde aqueous solution (35wt%), dripping time: 30min, and keep warm for 60min. After the reaction is completed, use sodium hydroxide solution (1wt%) to neutralize the reaction system to a pH of about 7. Lower the temperature to 60℃, add 1.5g of urea and react for 30min to remove the unreacted part of the unreacted formaldehyde. After cooling to room temperature, pour out the reactant, dialyze using a dialysis bag, and freeze-dry the dialyzed polymer solution for later use.
[0050] (2) Polyvinyl formal grafted ionomer:
[0051] Redissolve 10g of the polyvinyl alcohol formaldehyde polymer obtained by the above reaction in 100g of deionized water. Add 0.2g of potassium persulfate to the reactor containing the polyvinyl alcohol formal polymer solution, replace the air three times with vacuum and purge with nitrogen for 30min, and heat the reactor to 75°C. After the temperature is constant and the system is stirred evenly, control the dropwise addition time to 30min, and slowly add 3g of methyl methacrylate sulfobetaine for graft polymerization. After the reaction has reacted for 12h, stop the reaction. After cooling to room temperature, pour out the reactant, dialyze with a dialysis bag, and freeze-dry the dialyzed polymer solution for later use.
[0052] Example 3
[0053] This embodiment is basically the same as the embodiment 1, except that the temperature of the graft polymerization and the amount of the monomer are controlled to regulate the number of the polyion monomer side chains and the degree of polymerization.
[0054] (1) Preparation of polyvinyl formal binder:
[0055] Put 10g of polyvinyl alcohol (1799) into 100g of deionized water and stir continuously. Slowly heat to 90℃ and keep warm for 1h to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol aqueous solution. Adjust the temperature to 85℃, and start dripping dilute hydrochloric acid solution (0.1mol / L) to adjust the pH to about 2.5. Slowly drip 3.5g of formaldehyde aqueous solution (35wt%), dripping time: 30min, and keep warm for 120min. After the reaction is completed, use sodium hydroxide solution (1wt%) to neutralize the reaction system to a pH of about 7. Lower the temperature to 60℃, add 1.5g of urea and react for 30min to remove the unreacted part of the unreacted formaldehyde. After cooling to room temperature, pour out the reactant, dialyze using a dialysis bag, and freeze-dry the dialyzed polymer solution for later use.
[0056] (2) Polyvinyl formal grafted ionomer:
[0057] Redissolve 10g of the polyvinyl alcohol acetal polymer obtained by the above reaction in 100g of deionized water. Add 0.1g of potassium persulfate to the reactor containing the polyvinyl alcohol formal polymer solution, replace the air three times with vacuum and purge with nitrogen for 30min, and heat the reactor to 80°C. After the temperature is constant and the system is stirred evenly, control the dropwise addition time to 30min, and slowly add 5g of methyl methacrylate sulfobetaine for graft polymerization. After the reaction has reacted for 12h, stop the reaction. After cooling to room temperature, pour out the reactant, dialyze with a dialysis bag, and freeze-dry the dialyzed polymer solution for later use.
[0058] Example 4
[0059] This embodiment is basically the same as the embodiment 1, except that carboxybetaine methacrylate is selected as the grafting monomer instead of sulfobetaine methacrylate.
[0060] (1) Preparation of polyvinyl formal binder:
[0061] Put 10g of polyvinyl alcohol (1799) into 100g of deionized water and stir continuously. Slowly heat to 90℃ and keep warm for 1h to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol aqueous solution. Adjust the temperature to 85℃, and start dripping dilute hydrochloric acid solution (0.1mol / L) to adjust the pH to about 2.5. Slowly drip 3.5g of formaldehyde aqueous solution (35wt%), dripping time: 30min, and keep warm for 120min. After the reaction is completed, use sodium hydroxide solution (1wt%) to neutralize the reaction system to a pH of about 7. Lower the temperature to 60℃, add 1.5g of urea and react for 30min to remove the unreacted part of the unreacted formaldehyde. After cooling to room temperature, pour out the reactant, dialyze using a dialysis bag, and freeze-dry the dialyzed polymer solution for later use.
[0062] (2) Polyvinyl formal grafted ionomer:
[0063] Redissolve 10g of the polyvinyl alcohol acetal polymer obtained by the above reaction in 100g of deionized water. Add 0.1g of potassium persulfate to the reactor containing the polyvinyl alcohol formal polymer solution, replace the air three times with vacuum and purge with nitrogen for 30min, and heat the reactor to 75°C. After the temperature is constant and the system is stirred evenly, control the dropwise addition time to 30min, and slowly add 3g of methacrylic acid carboxybetaine for graft polymerization. After the reaction has reacted for 12h, stop the reaction. After cooling to room temperature, pour out the reactant, dialyze with a dialysis bag, and freeze-dry the dialyzed polymer solution for later use.
[0064] Example 5
[0065] This embodiment is basically the same as embodiment 1, except that butyraldehyde is selected as the acetalization reactant, and more non-polar side chains are introduced into the main chain.
[0066] (1) Preparation of polyvinyl butyral binder:
[0067] Put 10g of polyvinyl alcohol (1799) into 100g of deionized water and stir continuously. Slowly heat to 90℃ and keep warm for 1h to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol aqueous solution. Adjust the temperature to 85℃, and start dripping dilute hydrochloric acid solution (0.1mol / L) to adjust the pH to about 2.5. Slowly drip 3.5g of butyraldehyde solution (35wt%), dripping time: 30min, and keep warm for 120min. After the reaction is completed, use sodium hydroxide solution (1wt%) to neutralize the reaction system to a pH of about 7. Lower the temperature to 60℃, add 1.5g of urea and react for 30min to remove the unreacted part of the unreacted butyraldehyde. After cooling to room temperature, pour out the reactant, dialyze using a dialysis bag, and freeze-dry the dialyzed polymer solution for later use.
[0068] (2) Polyvinyl butyral grafted ionomer:
[0069] Redissolve 10g of the polyvinyl alcohol acetal polymer obtained by the above reaction in 100g of deionized water. Add 0.1g of potassium persulfate to the reactor containing the polyvinyl alcohol butyral polymer solution, replace the air three times with vacuum and purge with nitrogen for 30min, and heat the reactor to 75°C. After the temperature is constant and the system is stirred evenly, control the dropwise addition time to 30min, and slowly add 3g of methyl methacrylate sulfobetaine for graft polymerization. After the reaction has reacted for 12h, stop the reaction. After cooling to room temperature, pour out the reactant, dialyze with a dialysis bag, and freeze-dry the dialyzed polymer solution for later use.
[0070] Example 6
[0071] This example is basically the same as Example 1, except that polyvinyl alcohol (1788) is selected to replace polyvinyl alcohol (1799) as the main chain for acetalization and graft polymerization.
[0072] (1) Preparation of polyvinyl formal binder:
[0073] Put 10g of polyvinyl alcohol (1788) into 100g of deionized water and stir continuously. Slowly heat to 90℃ and keep warm for 1h to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol aqueous solution. Adjust the temperature to 85℃, and start dripping dilute hydrochloric acid solution (0.1mol / L) to adjust the pH to about 2.5. Slowly drip 3.5g of formaldehyde aqueous solution (35wt%), dripping time: 30min, and keep warm for 120min. After the reaction is completed, use sodium hydroxide solution (1wt%) to neutralize the reaction system to a pH of about 7. Lower the temperature to 60℃, add 1.5g of urea and react for 30min to remove the unreacted part of the unreacted formaldehyde. After cooling to room temperature, pour out the reactant, dialyze using a dialysis bag, and freeze-dry the dialyzed polymer solution for later use.
[0074] (2) Polyvinyl formal grafted ionomer:
[0075] Redissolve 10g of the polyvinyl alcohol acetal polymer obtained by the above reaction in 100g of deionized water. Add 0.1g of potassium persulfate to the reactor containing the polyvinyl alcohol formal polymer solution, replace the air three times with vacuum and purge with nitrogen for 30min, and heat the reactor to 75°C. After the temperature is constant and the system is stirred evenly, control the dropwise addition time to 30min, and slowly add 3g of methyl methacrylate sulfobetaine for graft polymerization. After the reaction has reacted for 12h, stop the reaction. After cooling to room temperature, pour out the reactant, dialyze with a dialysis bag, and freeze-dry the dialyzed polymer solution for later use.
[0076] Comparative Example 1
[0077] This comparative example is to directly use polyvinyl alcohol (1799) as the main binder, dissolve it in deionized water for use, and carry out performance testing and preparation of slurry and electrode.
[0078] Comparative Example 2
[0079] The steps of this comparative example are basically similar to those of Example 1, except that the ether bond structure is introduced into the polyvinyl alcohol (1799) only by formalization on the main chain, and the grafting introduction of the ionic monomer is omitted.
[0080] Comparative Example 3
[0081] The steps of this comparative example are basically similar to those of Example 1, except that only the side chains of polyion monomers are introduced into polyvinyl alcohol (1799) by graft polymerization, and the introduction of ether bonds on the main chain is omitted.
[0082] Effect Example
[0083] The following describes the performance of the comparative examples and embodiments.
[0084] Preparation of electrode sheets: Nano-silicon, conductive carbon black and binder are homogenized in a ratio of 7:1:2, and the slurry is evenly scraped on a 0.1 mm copper foil using a 100 μm scraper; then transferred to an 80°C forced air oven and dried for 12 hours to obtain the electrode sheet to be used.
[0085] Peeling force test: The adhesive tape used is 3M tape, and the electrode sample is cut into a 19×5cm shape. Then the cut electrode is attached to the glass sheet with double-sided tape and the electrode and reverse peeling force tests are performed using a 180° tensile test. The peeling speed is 60mm / min.
[0086] Conductivity test: The polymer solution is baked into a film with a thickness of about 0.1mm using a polytetrafluoroethylene mold, and cut into discs with a diameter of 18mm using a cutter for standby use. The battery is assembled in the form of positive electrode shell-steel sheet-electrolyte-film-electrolyte-steel sheet-shrapnel-negative electrode shell; the electrolyte used is an electrolyte prepared with a volume ratio of 1:1 of ethylene carbonate (EC) and diethyl carbonate (DEC), plus 10% fluoroethylene carbonate (FEC) as a solvent, and 1M lithium hexafluorophosphate (LiPF6) as a lithium salt. The battery assembly is carried out in a glove box (H2O≤0.1ppm, O2≤0.5ppm). Before the test, the battery is left at room temperature for 24h. Then the conductivity is tested using an electrochemical workstation.
[0087] Cycle test: Similarly, the battery used in the cycle test is also completed in the glove box. The assembly order is positive electrode shell-negative electrode sheet-electrolyte-diaphragm-electrolyte-lithium sheet-steel sheet-shrapnel-negative electrode shell. The electrolyte used is the same as that used above. The cycle test uses the Xinwei test channel to perform constant current charge and discharge tests on the battery at 30°C. The charge and discharge current density is 0.2C. Before the test begins, the battery needs to be left to stand for 12 hours.
[0088] The results are as follows Figure 1 and Figure 2 shown.
[0089] Figure 1 The coulombic efficiency corresponding to the 0.2C long cycle of the electrode in Example 4. The first coulombic efficiency of the battery reached 88.86%, and the coulombic efficiency in the subsequent 150 cycles was higher than 98.5%, with a good reversible cycle. Figure 2 It can be observed from the cycle specific capacity curve that the initial discharge specific capacity of the nano silicon electrode of Example 4 is as high as 3409.9 mAh g-1, and after 4 cycles of low current activation, the initial cycle specific capacity at 0.2C is also 2990.4 mAh g-1. After 146 cycles at a current density of 0.2C, it still has a high capacity of 1929.0 mAh g-1, and the capacity retention rate is as high as 64.5%, which shows that the electrode prepared in Example 4 has an excellent cycle stability performance of a nano silicon negative electrode.
[0090] Peel force and ionic conductivity:
[0091] Test items Average peel force (N) Ionic conductivity (mS / cm) Example 1 14.30 0.0175 Example 2 14.43 0.0313 Example 3 14.40 0.0205 Example 4 14.35 0.0227 Example 5 12.18 0.0108 Example 6 11.55 0.0156 Comparative Example 1 12.00 0.0014 Comparative Example 2 13.21 0.0133 Comparative Example 3 12.55 0.0092
[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. The present invention has been described in detail with reference to the above embodiments, and those skilled in the art should understand that the technical solutions of the above embodiments are reasonably deleted, modified, replaced and optimized; and these deletions, modifications, replacements and optimizations do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a silicon-based negative electrode binder with a dual ion-conducting network having a self-repairing function, characterized in that: Taking polyvinyl alcohol as the main component, ether bonds are introduced into the chain segments by acetalization reaction, and then the polyvinyl alcohol acetal is introduced into the side chain of the polyion monomer by graft polymerization reaction; The specific method is: (1) Preparation of polyvinyl acetal binder: Put polyvinyl alcohol into deionized water and continue stirring, slowly raise the temperature to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol aqueous solution; when the temperature is adjusted to a first treatment temperature, add a hydrochloric acid solution to a first pH value; then slowly add an aldehyde substance solution to keep the temperature for reaction; after the reaction is completed, adjust the pH of the reaction system to neutral; when the temperature drops to a second treatment temperature, add urea to remove unreacted aldehyde substances; after the temperature drops to room temperature, pour out the reactant, dialyze using a dialysis bag, and freeze-dry the dialyzed polymer solution for later use; the amount of the aldehyde substance added is 5% to 40% of the molar number of hydroxyl groups in the polyvinyl alcohol; (2) Polyvinyl acetal grafted ionomer: The polyvinyl alcohol acetal polymer obtained by the above reaction is redissolved in deionized water; then an initiator is added, the air is replaced by vacuum for three times and purged, and the reactor is heated to the set reaction temperature; after the temperature is constant and the system is stirred evenly, the monomer solution is slowly added dropwise at a controlled dropping time to carry out a graft polymerization reaction; after the reaction, the reaction is stopped; after cooling to room temperature, the reactant is poured out, dialyzed using a dialysis bag, and the dialyzed polymer solution is freeze-dried for later use.
2. The method for preparing a silicon-based negative electrode binder having a dual ion-conducting network with self-repairing function according to claim 1, characterized in that: The polymerization degree of the polyvinyl alcohol is 600-2500, and the alcoholysis degree is 50%-99%.
3. The method for preparing a silicon-based negative electrode binder having a dual ion-conducting network with self-repairing function according to claim 1, characterized in that: In the acetalization reaction, the conversion degree of the hydroxyl group by the acetalization reaction using the aldehyde substance is 5% to 50%.
4. A method for preparing a silicon-based negative electrode binder having a dual ion-conducting network with self-repairing function according to claim 1 or 3, characterized in that: The aldehyde substance has an aldehyde structure, and the aldehyde structure includes one or more of formaldehyde, acetaldehyde, propionaldehyde, and butyraldehyde.
5. The method for preparing a silicon-based negative electrode binder having a dual ion-conducting network with self-repairing function according to claim 1, characterized in that: The graft polymerization uses an initiator to initiate the monomer to carry out graft polymerization on the polyvinyl alcohol acetal chain, and the mass ratio of the grafted body to the grafted monomer is 10:1 to 1:10; the mass ratio of the initiator to the monomer is 1:1000 to 5:100; The initiator includes one or more of ammonium persulfate, potassium persulfate, alkali metal persulfate-reducing agent, azobisisobutylamidine hydrochloride AIBA, azobisisobutylimidazoline hydrochloride AIBI, azobiscyanovaleric acid ACVA, and azobisisopropylimidazoline AIP; the reducing agent is selected from sodium bisulfite NaHSO3, sodium sulfite Na2SO3, sodium thiosulfate Na2S2O3 or oxalic acid.
6. A method for preparing a silicon-based negative electrode binder having a dual ion-conducting network with self-repairing function according to claim 1 or 5, characterized in that: In the graft polymerization, the monomers include one or more of dimethyldiallylammonium chloride DMDAAC, methacryloyloxyethyltrimethylammonium chloride DMC, acryloyloxyethyltrimethylammonium chloride DAC, methacrylamidepropyltrimethylammonium chloride MAPTAC, 2-acrylamido-2-methylpropanesulfonic acid AMPS, acrylic acid AA, itaconic acid IA, sodium styrene sulfonate NaSS, sodium α-olefin sulfonate, 2-methacryloyloxyethylphosphorylcholine MPC, carboxybetaine acrylamide CBAA, methacrylic acid sulfobetaine SBMA, and methacrylic acid carboxybetaine CBMA.
7. The method for preparing a silicon-based negative electrode binder having a dual ion-conducting network with self-repairing function as claimed in claim 1, characterized in that: In step (1), the first treatment temperature is 50-100°C, the first pH value is 1-6; the dropwise addition time is 5-60 minutes; the reaction time is 1-6 hours; the concentration of the aldehyde solution is 5%-60%; the second treatment temperature is 30-70°C; and the second pH value is 7-10.
8. The method for preparing a silicon-based negative electrode binder having a dual ion-conducting network with self-repairing function as claimed in claim 1, characterized in that: In step (1), the alkaline solution for adjusting pH includes one or more of LiOH, NaOH, KOH, NaOH, and NH3·H2O.
9. The method for preparing a silicon-based negative electrode binder having a dual ion-conducting network with self-repairing function as claimed in claim 1, characterized in that: In step (2), the reaction temperature is 50-100° C.; the dropwise addition time is 5-120 min; and the total reaction time is 1-12 h.
10. A silicon-based negative electrode binder having a dual ion-conducting network and having a self-repairing function obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
An aqueous binder for lithium-ion battery anode materials and its preparation method
CN110336037B
Application of melamine cross-linked polyvinyl alcohol hydrogel as lithium battery silicon negative electrode binder
CN110444765A
Binder, preparation method of binder, electrode plate and secondary battery
CN112680148A
Method for improving performance of high-specific-energy silicon monoxide negative electrode by using lithium ion modified binder
CN113782744A
Lithium ion battery composite binder and preparation method and application thereof
CN114203987A
Cited By
Binder for diaphragm, preparation method of binder, modified diaphragm and battery
CN121022312A